Application of Ergonomics in the Field of Waste Management (Case Study : Waste4Change) - Adikuasa, Muhammad Biyadihie; Riyanto, Hendro Ardiansyah; Putri, Fairus Jelita Regita; Junerosano, Mohamad Bijaksana (Faculty of Civil Engeneering and Planning - ITATS, 2023)
One of the serious environmental problems the Indonesian people face today is the waste problem. Waste separation is still an effective solution to facilitate the next waste-handling process. In Indonesia, most of the work of waste sorting is done manually, causing work risks, one of which is related to ergonomics at work. Ergonomics is a work rule or norm that can bring comfort and productivity to work. Waste4Change is a social entrepreneurship that provides responsible waste management services. This research aims to improve ergonomics and working methods in waste separation at Waste4Change. A combination of literature review and field studies is used as the research method. The results showed that waste separation by sitting for too long causes pain in the waist and back of workers. Additionally, the repetitive combination of sitting and standing movements when collecting waste for further separation is felt to be slow and inefficient. The solution to this problem is providing a sorting table made of stainless steel with a height of 100 cm, which is adjusted to the average height of waste sorting workers at Waste4Change. By using the sorting table method, the work of sorting waste is more effective and healthier for the bodies of the waste sorters